(untitled) (Anclajes, 2023)
The main trip of the Salvadoran writer Roque Dalton to Eastern Europe took place in 1966 and was destined for Prague. That experience was captured in the collection of poems Taberna y otros lugares (1969). The volume analyzed as constitutes a testimony of imagination about Prague and about the Czechoslovak Socialist Republic in the socio-political context of the Cold War. The book is part of the so-called "world communist literature", but it nevertheless adopts a critical and desacralizing perspective within this literature.